2012
DOI: 10.1080/13527258.2012.738698
|View full text |Cite
|
Sign up to set email alerts
|

‘Born in the Republic of Austria’ The invention of rock heritage in Austria

Abstract: This article explores the retrospective cultural consecration of popular music in Austria. Examining two recent documentary projects, one focusing on Austropop, a Viennese popular music phenomenon of the early 1970s, and the other on the punk-inspired music scene of Linz in Upper Austria from late 1970s, the article shows how both projects seek to invent an Austrian popular music heritage and advance claims for national or regional cultural identity based on the discourse of rock heritage. 'Weltberühmt in Öste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Traditionally, European identity and cultural heritage are seen in connection to high culture (Cohen 2013, Lähdesmäki 2012. More recently, however, various studies (Bennett 2009, Reitsamer 2014, Brandellero and Janssen 2014 have demonstrated that due to the blurring of the boundaries between 'high' and 'low' culture and the attention paid to social history, heritage discourses increasingly include popular music as an expression of shared identity. Nevertheless, there has thus far been little discussion of the European dimensions of popular music heritage (Cohen 2013 being a notable exception).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Traditionally, European identity and cultural heritage are seen in connection to high culture (Cohen 2013, Lähdesmäki 2012. More recently, however, various studies (Bennett 2009, Reitsamer 2014, Brandellero and Janssen 2014 have demonstrated that due to the blurring of the boundaries between 'high' and 'low' culture and the attention paid to social history, heritage discourses increasingly include popular music as an expression of shared identity. Nevertheless, there has thus far been little discussion of the European dimensions of popular music heritage (Cohen 2013 being a notable exception).…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, narratives of popular music heritage are not only connected to generational identities, but are also linked to notions of place. For example, museums (Burgoyne 2003), documentaries (Reitsamer 2014) and tourist organizations (Brandellero and Janssen 2014) give shape to popular music as a form of local and national heritage.…”
Section: Introductionmentioning
confidence: 99%
“…Again, to fully understand the meaning of this distinction and how it differs across countries, national historical and cultural repertories are the key interpretative tool. It is clear that Austrian and English taste groups reflect tension between young people with a preference for popular emerging styles as opposed to the more traditional tastes of folk and classical of the more adult population (Savage 2006;Reitsamer 2012). However, Israeli and Serbian groups are structured differently.…”
Section: 5mentioning
confidence: 99%
“…Austria has a significant musical legacy: in addition to preserving a strong folk tradition, it is considered by many to be the European capital of western classical music. However, tensions exist here between supporters of traditional folk, schlager and volkstumliche folk-pop ballads, American-and Britishinfluenced rock and hip-hop, and hybrid world music (Reitsamer 2012). England features widely in the literature on culture and social stratification.…”
Section: Cultural Research: a Cross-national Perspectivementioning
confidence: 99%
See 1 more Smart Citation